Genetic Diversity and Phylogeny of Aedes aegypti, the Main Arbovirus Vector in the Pacific. - Elodie Calvez; Laurent Guillaumot; Laurent Millet; Jérôme Marie; Hervé Bossin; Vineshwaran Rama; Akata Faamoe; Sosiasi Kilama; Magali Teurlai; Françoise Mathieu-Daudé; Myrielle Dupont-Rouzeyrol (Public Library of Science (PLoS), 2016)
BACKGROUND:The Pacific region is an area unique in the world, composed of thousands of islands with differing climates and environments. The spreading and establishment of the mosquito Aedes aegypti in these islands might be linked to human migration. Ae. aegypti is the major vector of arboviruses (dengue, chikungunya and Zika viruses) in the region. The intense circulation of these viruses in the Pacific during the last decade led to an increase of vector control measures by local health authorities. The aim of this study is to analyze the genetic relationships among Ae. aegypti populations in this region. METHODOLOGY/PRINCIPAL FINDING:We studied the genetic variability and population genetics of 270 Ae. aegypti, sampled from 9 locations in New Caledonia, Fiji, Tonga and French Polynesia by analyzing nine microsatellites and two mitochondrial DNA regions (CO1 and ND4). Microsatellite markers revealed heterogeneity in the genetic structure between the western, central and eastern Pacific island countries. The microsatellite markers indicate a statistically moderate differentiation (FST = 0.136; P < = 0.001) in relation to island isolation. A high degree of mixed ancestry can be observed in the most important towns (e.g. Noumea, Suva and Papeete) compared with the most isolated islands (e.g. Ouvea and Vaitahu). Phylogenetic analysis indicated that most of samples are related to Asian and American specimens. CONCLUSIONS/SIGNIFICANCE:Our results suggest a link between human migrations in the Pacific region and the origin of Ae. aegypti populations. The genetic pattern observed might be linked to the island isolation and to the different environmental conditions or ecosystems.